Why Central Asia’s Mushiston is not a source for the Late Bronze Age tin ingots from the Uluburun shipwreck - Berger, Daniel; Kaniuth, Kai; Brügmann, Gerhard; Pernicka, Ernst (Frontiers in Earth Science, 2023)
Tin was a crucial commodity in prehistory to produce bronze, and knowledge of the origins of this metal is important for understanding cultural relations and the complexity and extent of trade. However, many aspects of the provenance of tin are still not resolved. A recent study by Powell et al. in Science Advances 8(48) examined the historically significant tin ingots from the Uluburun shipwreck, which are key to the economy and long-distance trade of tin in the Late Bronze Age Mediterranean and beyond. Isotopic and chemical data of the objects was collected, from which a tin origin from Central Asia, particularly Mushiston in Tajikistan, and Anatolia was reconstructed. The study thereby proposed a solution to the long-standing riddle of tin provenance via scientific reasoning and comparative data. While this avenue of investigation is intriguing, this article maintains that the authors’ arguments do not support their far-reaching conclusions. Instead, it emphasises the similarities with Late and Middle Bronze Age tin ingots from Israel and Britain, and suggests a common origin of part of the Uluburun cargo with these items. South-west England is considered a very likely source region, but other tin ingots of the Uluburun wreck could also originate from Afghanistan and perhaps somewhere else.